A domestic solution for transboundary harm: Singapore's haze pollution law - MOHAN, Mahdev (Institutional Knowledge at Singapore Management University, 2017)
Toxic ‘haze’ from fires, often burning over dry peatland in Indonesia, has affected millions across Indonesia, Singapore and Malaysia, as well as parts of the Philippines and Thailand. For Singapore in particular, this slash-and-burn method of clearing land in Indonesia to cultivate crops such as oil palm has been an annual problem since 1972. However, 2015 stands out as the year Singapore experienced one of its worst episodes of haze pollution. Air quality based on the Pollutant Standards Index (PSI) plummeted to the ‘very unhealthy’ and ‘hazardous ranges’ for close to 50 days. Singapore suffered an estimated SGD $700 million in economic losses in 2015 as a result of, inter alia, the closure of schools, hotels, tourist attractions and major sporting events. Moreover, the large quantities of carbon dioxide released set back Southeast Asia’s efforts to mitigate climate change. A scientific study has shown that the 2015 fires in Indonesia released nearly one gigaton of greenhouse gases. Daily emissions during that haze period were even higher than that of all the European Union member states put together.